Rethinking the Role of Nitroglycerin Ointment in Ischemic Vascular Filler Complications: An Animal Model With ICG Imaging. Issue 2 (March 2016) - Hwang, Catherine J.; Morgan, Payam V.; Pimentel, Aline; Sayre, James W.; Goldberg, Robert A.; Duckwiler, Gary
Abstract : Purpose: Soft tissue dermal fillers, both temporary and permanent, are used frequently in facial rejuvenation. As the use of fillers increases, ischemic complications including skin necrosis are becoming more prevalent. In the literature, topical nitroglycerin paste has been recommended in the early treatment of patients presenting with ischemia. The purpose of this study was to evaluate the vascular perfusion effects of topical nitroglycerin paste in an animal model using indocyanine green (ICG) imaging. Methods: After Animal Research Committee approval, a rabbit ear model was used to create filler-associated skin ischemia. Ischemia was confirmed to occur after intra-arterial occlusion. Four commonly used soft tissue fillers were injected intra-arterially: Radiesse (Merz USA, Greensboro NC), Restylane (Galderma, Ft. Worth, TX), Juvederm Ultra (Allergan, Irvine CA), Belotero (Merz USA, Greensboro NC) (0.1 ml). A total of 15 ears were used, 1 control and 4 experimental per product. Thirty minutes after occlusion, nitroglycerin ointment USP, 2%(Nitro-Bid) was applied topically to the experimental ears. Vascular perfusion was evaluated with the SPY System (Novadaq Inc.) using ICG imaging. Perfusion images were obtained at baseline, immediately after, and 30 minutes after intra-arterial filler injection, and at 30, 60, 90, and 120 minutes after application of topical nitroglycerin ointment. Results: In this rabbit ear model, no statistically significant improvement in perfusion was noted after topical application of nitroglycerin paste with ICG imaging. In addition, the skin of the rabbit ear post-nitroglycerin ointment appeared to have more of a congested appearance than the controls. Conclusions: Ischemic filler complications are becoming increasingly prevalent. Practitioners often treat these complications with topical nitroglycerin paste based on the knowledge that topical nitroglycerin causes vasodilation. In filler-induced tissue ischemia, however, filler product is present within arterioles. Theoretically, applying nitroglycerin paste, at least early, may not improve perfusion and could worsen ischemia with dilation of vessels and further propagation of product into the smaller arterioles and capillaries. In addition, nitroglycerin paste has systemic effects, including hypotension and dizziness, which may not be tolerated by some patients. Therefore, the authors caution the use of topical nitroglycerin paste in patients presenting with filler-associated ischemia. Further studies in the best treatment algorithms for patients presenting with ischemic complications need to be performed. Abstract : The use of topical nitroglycerin paste for the treatment of early ischemic filler complications may not improve the perfusion in ischemic areas. We caution the use of nitroglycerin paste in patients presenting with ischemic filler complications.